Implementation of Cooperative Learning Model Learning Through The STAD Method in Improving Student’s Critical Thinking Ability - Iin Khairunnisa; Muhammad Thariq Aziz (IJECA (International Journal of Education and Curriculum Application), 2019)
This study is about the application of Cooperative Learning models through the STAD method to improving students' critical thinking. The problem in this study was the low critical thinking of students about eleven-class economic subjects in the social studies program at one of the secondary schools in Sukabumi City. The research method used was a quasi experiment with research design The Pre-Equivalent Pre-test - Post Design Control-Test Group. Based on the test for normality, homogenies, and t-test from the pre-test post-test data, the students understood the concept of the experimental class and the control class. The sampling technique used was purposive sampling. Data collection uses tests and assignments. The results of this study were tested with one-way Anava. The results of the study are as follows. 1) Cooperative learning model STAD method is effective for increasing interest and learning outcomes (Critical Thinking) Economic Subjects, 2) STAD learning model in class XI IPS A is more effective in increasing student learning interest compared to STAD method in class XI IPS B, while Method STAD in class XI IPS B is more effective to improve student learning outcomes compared to Class XI IPS A.